Lifestyle correlates of musical preference: 1. Relationships, living arrangements, beliefs, and crime - North, Adrian; Hargreaves, David (Sage Publications Ltd., 2007)
Several studies indicate that musical preferences provide a means of discriminating between social groups, and suggest indirectly that musical preferences should correlate with a variety of different lifestyle choices. In this study, 2532 participants responded to a questionnaire asking them to state their musical preference and also to provide data on various aspects of their lifestyle (namely interpersonal relationships, living arrangements, moral and political beliefs, and criminal behaviour). Numerous associations existed between musical preference and these aspects of participants’ lifestyle. The nature of these associations was generally consistent with previous research concerning aputative liberal–conservative divide between differing groups of fans. It is concluded that participants’ musical preferences provided a meaningful way of distinguishing different lifestyle choices.